Surveying tropical glacier change on Puncak Jaya (Irian Jaya/West Papua, Indonesia) in recent years using multispectral high-resolution satellite imagery, publishing updated map of change 1850-2024 - Ibel, David; Mölg, Thomas; Sommer, Christian (PANGAEA, 2025)
Glaciers have been retreating for many decades on a global scale due to anthropogenic climate change, including the mostly small glaciers in the Tropics. In this paper, we document area changes of the Puncak Jaya glaciers in South-East Asia on West Papua, Indonesia, until the present. The survey was done using using high resolution multispectral satellite imagery of PlanetScope and Pléiades missions from 2023 and 2024. Additionally, we digitized and georeferenced historical glacier accounts from analogue maps, resulting in a new overview map of glacier change on Puncak Jaya since 1850, and some further delineation was performed ranging from 2002 to 2023 to complete the map. The results show a decrease of total glacier surface area by more than 99% since 1850 and by 64% since the last survey in 2018. Current glacier area (in 2024) amounts to 0.165 km². The development of Puncak Jaya glaciers is thus in line with the global development of (tropical) glaciers. Assuming the current area retreat rates to continue, it is very likely that Puncak Jaya glaciers will disappear around 2030.
Keywords: Carstensz; historical glacier change; Indonesia; Irian Jaya; Northwall Firn; Papua; Puncak Jaya; remote sensing of glaciers; Southeast Asia; South East Asia; Tropical Climate; tropical glacier